THE ROLE AND INVOLVEMENT OF BUSINESS AND INSTITUTIONAL OPERATORS IN PROMOTING LOCAL INVESTMENT AND ECONOMIC GROWTH BY ACCESSING AND USING GRANTS. MEASURES AND COURSES OF ACTION - Gabroveanu (Vladoi), Janina Mirela; Stefanescu, Alexandru (Annals of Spiru Haret University. Economic Series, 2017)
Starting from the premise that sustainable development is an overall objective of EU Member States,that can be achieved through international cooperation that aims at economic growth, social development and environmental protection, the European Commission analyzed the socio-economic and investment context of the member states, identified risks and opportunities and made some recommendations. This paper presents the best practices of the European funding system to improve the accountability of business or institutional operators accessing European funds and the measures taken by some Member States for good governance. We emphasize the need to know the socio-economic and investment context by all stakeholders and initiate concrete measures of action to ensure real and sustainable economic growth by identifying feasible and lasting solutions; what is the role of business or institutional operators at local and regional level and how it could ensure good governance at local and regional level by applying for grants.